Watch her - Hill, Edwin, 1970- (Hill, Edwin, 1970- Hester Thursby mystery., 2021)
Investigating a suspicious burglary and the disappearances of Prescott University alumni, Harvard librarian Hester Thursby and Detective Angela White uncover financial transgressions, rumors of infidelity, and a decades-old tragedy.